Effect of probiotic and prebiotic supplementation with or without animal protein concentrate on performance of female quails - Ahmad, Hiyam Mohmmod; AL-Neemi, Mohammad Ibrahim (Sulaimani Journal for Pure and Applied Sciences, 2018)
The aim of this experiment was to determine the effect of supplementation of probiotic and prebiotic in egg production ration with or without animal protein concentrate on production performance of quail females. One hundred and sixty birds 70 days old were randomly distributed to eight treatments (20 bird/ treatment; 5 replicates/ each). T1: basal ration contain 5% animal protein concentrated without supplementation of probiotic or prebiotic; T2: basal ration without animal protein concentrated, probiotic and prebiotic; T3: T1 + 0.10% probiotic; T4: T1 + 0.10% prebiotic (Yeast); T5: T1 + 0.10% probiotic + 0.10% prebiotic; T6: T2 + 0.10% probiotic; T7: T2 + 0.10% prebiotic; T8: T2 + 0.10% probiotic + 0.10% prebiotic. Results showed that no significant differences were found among treatments in egg production (HDP %), egg weight, egg mass, feed intake, feed conversion ratio and energy conversion ratio, but energy consumption in T5 were significantly (P≤0.05) higher than T7. Significant (P≤0.05) differences were found between treatments in egg quality (yolk weight (g), albumin weight (%), shell thickness (mm), and shell weight (g and %). Whereat, T1 was significantly (P≤0.05) higher than T6 in egg specific gravity, also T1 was significantly (P≤0.05) higher than T2 in shape index. T1 and T2 significantly (P≤0.05) higher than the other treatments in yolk index. While in albumin index T3 and T4 Significantly (P≤0.05) higher than T6. Albumin weight percentage in T2, T5, T6 and T7 were significantly (P≤0.05) higher than T1. Egg surface area was significantly (P≤0.05) higher in T3 compared with T2, T7 and T8. Shell weight (g) was significantly (P≤0.05) higher in T1 (control) than T6 and T7, while T6 was significantly (P≤0.05) higher than T8 in shell thickness.
Keywords: Probiotic; Prebiotic; Quail Female Performance